Through the Looking Glass of History: A New Vision for Labor Education. Issue 4 (December 2015) - Mantsios, Gregory
Abstract : This article explores the potential of labor education in the context of significant challenges: It examines a number of historical and contemporary models and suggests building on those models to develop a new framework for the field of labor education that is more comprehensive and conceptually different from the one generally employed. The author argues for a broader definition of Labor Studies (one that is community oriented), envisions a wider role for labor educators (one that includes engagement with workforce development initiatives), and calls for labor colleges or labor schools to be established with public funding both nationally and locally.